2003
DOI: 10.1073/pnas.0831001100
|View full text |Cite|
|
Sign up to set email alerts
|

3β-Acetoxyandrost-1,5-diene-17-ethylene ketal functions as a potent antiandrogen with marginal agonist activity

Abstract: The majority of available antiandrogens have been reported to possess agonist activity to induce prostate-specific antigen, which might result in antiandrogen withdrawal syndrome. Here we report the identification of 3β-acetoxyandrost-1,5-diene-17-ethylene ketal (ADEK) from dehydroepiandrosterone metabolites and derivatives as a potent antiandrogen. We found ADEK could interrupt androgen binding to the androgen receptor (AR) and suppress androgen-induced transactivations of WT AR and a mutant AR in prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…We showed that many DHEA metabolites, including ADEK, possess some estrogen activity, 15,16 suggesting that ADEK might cause not only castration effect but also some side effects, such as cardiovascular toxicity in vivo. Because of these unfavorable side effects, estrogens (e.g., DES) are rarely used as first-line hormonal treatment in spite of the evidence suggesting an additional benefit, a direct cytotoxic effect of estrogens through both estrogen receptor (ER)-dependent and ER-independent pathways in prostate cancer cells.…”
Section: Hormone Specificity Of Steroid Derivativesmentioning
confidence: 97%
See 4 more Smart Citations
“…We showed that many DHEA metabolites, including ADEK, possess some estrogen activity, 15,16 suggesting that ADEK might cause not only castration effect but also some side effects, such as cardiovascular toxicity in vivo. Because of these unfavorable side effects, estrogens (e.g., DES) are rarely used as first-line hormonal treatment in spite of the evidence suggesting an additional benefit, a direct cytotoxic effect of estrogens through both estrogen receptor (ER)-dependent and ER-independent pathways in prostate cancer cells.…”
Section: Hormone Specificity Of Steroid Derivativesmentioning
confidence: 97%
“…6,9,11,16,17 PSA-Luc containing a natural 6.0 kb promoter and a synthetic (ARE)4-Luc containing 4 copies of androgen response element (ARE) were kindly provided by Dr. A. Mizokami (Kanazawa University, Kanazawa, Japan) and Dr. M.L. Lu (Harvard Medical School, Boston, MA), respectively.…”
Section: Chemicals and Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations